1994
DOI: 10.1143/jjap.33.l1031
|View full text |Cite
|
Sign up to set email alerts
|

Organic Molecular Beam Deposition of α-Sexithienyl

Abstract: We study a quasicontinuum system for which there exists a sparse dressed state composed of the ground state and a single state of the true continuum. In general, the loss of population from the ground state to a true continuum via the quasicontinuum is total. In a special case, however, population is trapped in the ground state and the sparse dressed state is replaced by a trapping state containing no contribution from the true continuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…If we now restrict the study to films with granular structure we have shown that during deposition the grain size and ordering within the grains increases rapidly with increasing substrate temperature [29,37,69]. In all cases, the height of the steps of the films morphology measured by AFM show that, whatever the dimensions of the grains, T 6 molecules are standing approximately upright on the substrate.…”
Section: Morphology-dependent Polarization Of Fluorescence and Electrmentioning
confidence: 92%
See 1 more Smart Citation
“…If we now restrict the study to films with granular structure we have shown that during deposition the grain size and ordering within the grains increases rapidly with increasing substrate temperature [29,37,69]. In all cases, the height of the steps of the films morphology measured by AFM show that, whatever the dimensions of the grains, T 6 molecules are standing approximately upright on the substrate.…”
Section: Morphology-dependent Polarization Of Fluorescence and Electrmentioning
confidence: 92%
“…I 1,1 is the interaction exchange integral between translationally equivalent molecules I 1Y1 hU Ã 1 U 1 jV 1Y1 jU 1 U Ã 1 i, where the operator V 1,1 is the intermolecular potential energy), while I 1,2 , I 1,3 , and I 1,4 are the interaction exchange integrals between translationally non-equivalent molecules. The simplified excitonic molecule model [27] predicted a splitting as large as 1 eV of the 1 1 B u molecular level [28,29,156 6 Electronic Structure and Energy Transfer in Solid a-Sexithienyl 30]. A more refined approach uses the two-centers potential expansion, which considers the interaction between point multipoles located at the centers of the two charge distributions.…”
Section: Single Crystal Electronic Structurementioning
confidence: 99%
“…3 The standing structure was also reported by other groups. 4 Compared with the oligothiophenes on insulating substrates, there has been little investigation of oligothiophenes on metal substrates. Recently, however, studies of organic films on metal substrates have begun to investigate the organic-metal interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Among organic molecules, ␣-hexathiophene (T6) is a well-characterized prototypical compound for polyconjugated systems. [5][6][7][8][9][10][11][12] Furthermore, T6 possesses interesting properties of hole injection into highly fluorescent polymers. 13 It is then of utmost importance, in order to engineer new materials with suitable optoelectronic properties, to understand the essential processes in which T6 molecules form solid structures and to what extent their order can be driven by the substrate structure.…”
mentioning
confidence: 99%